Evaluation of a depression care model for the hill tribes: a family and community-based participatory research - Singkhorn, Onnalin; Hamtanon, Pawadee; Moonpanane, Katemanee; Pitchalard, Khanittha; Sunsern, Rachanee; Leaungsomnapa, Yosapon; Phokhwang, Chananan (BMC psychiatry, 2023)
Even though, there is a particularly high prevalence of depression among individuals from the hill tribes in northern Thailand, they are unable to receive appropriate intervention due to cultural, transportation, communication, and legal barriers. Using community-based participatory research (CBPR), a depression care model was developed for the hill tribe population. The effectiveness of this model was examined using questionnaires, observations, focus groups, and in-depth interviews. Participants include people with depression (n = 17) who were chosen based on their mild to moderately severe depression scores on the Patient Health Questionnaire 9-item (PHQ-9 scores of 5-19) and their caregivers (n = 5). The in-depth interview was conducted to distinguish the selected participants into two groups. The first group, the self-help group program, consisted of 12 participants endorsing negative thoughts about themselves and inappropriate problems solving. The second group, the family camp program, had ten participants, including five patients with family-related issues and their family members. Subjects separately participated in either the self-help or the family groups over three weeks. They completed the PHQ-9 at the beginning and end of the intervention. Questionnaires, observations, focus groups, and in-depth interviews were used to evaluate the effectiveness of the model. Content analysis was used to examine the qualitative data. Wilcoxon signed-rank test was used to analyze the changes in the severity of depression before and after participation in the intervention. The depression scores on the PHQ-9 of 12 participants improved significantly (11.92 ± 1.08 vs. 3.08 ± 0.51; p = 0.002) following participation in the self-help group. Increased self-esteem and improved interpersonal relationships were reported by participants in the self-help group program during interviews. There was no significant difference in the depression scores of 10 participating in the family camp program (6.00 ± 3.83 to 5.30 ± 3.56; p = 0.161). A model for depression care was tested in a hill tribe community, and its effectiveness was clearly observed. The developed model can be applied to other hill tribe communities in northern Thailand to improve depression care.